National Metrology Institute Of Malaysia / Muhammad Afiq Azmi - Azmi, Muhammad Afiq (Faculty Of Chemical Engineering, 2021)
The 17 weeks in NMIM Sepang was a memorable and honorable experience. The opportunity given to conduct the practical training at NMJM is truly a blessing as there were many advantages and new knowledge gained whilst working in the company. The staffs are very friendly as they gave a warm welcome when first arrived. Furthermore, they were very willingly to aid and share their knowledge and experience. Even though pH can often be regarded as simple, there is more behind it and if study thoroughly can be complex as their is such a great deal that could be discovered. The study of pH plays a great deal in not only the survival of human beings but many more such as the quality of products. Overall, in the time spent in the company was highly beneficial as new experience were gathered not only on the measurements of pH but also the methods of producing pH buffers. During the time spent, it was realized that temperature play a huge role in the measurement of -pH as H can effect the measurements with the slightest change in temperature. Hence, the supervisor, Encik Khirul Anuar, had advised to monitor and record the temperature of the lab daily. In addition, the opportunity to conduct and operate the pH meter was very knowledgeable and will someday be benefitted. It was clear that operating the pH meter can be a difficult task as there were uncertainties during the experiment. All in all, the time and knowledge gained during the internship was eye opening and it was profitably